Manajemen Konflik Penggunaan Sumber Daya Perikanan Antara Nelayan Tradisional Dan Industri - Rendi (CV. SINAR HOWUHOWU, 2025)
Conflict between traditional fishers and the fishing industry is a complex and frequent issue in coastal areas of Indonesia. This study aims to analyze the primary causes of the conflict, its impacts, and conflict management approaches that can foster sustainable and equitable fisheries resource management. A qualitative approach was employed, involving in-depth interviews, focus group discussions, participatory observations, and document analysis. The findings indicate that the conflict is mainly driven by unequal access to resources, differing interests between traditional fishers and the industry, and regulations that inadequately accommodate small-scale fishers. Conflict management based on co-management involving all stakeholders has proven effective in reducing tensions and enhancing the sense of ownership over marine resources. However, major challenges include economic and political power imbalances between traditional fishers and the industry. The study recommends strengthening community capacities, increasing participation in policymaking, and developing fair and inclusive regulations. Effective conflict management thus supports the sustainability of fisheries resources while improving the welfare of coastal communities.